Critical Thinking Skills Toward Ecological Problems of Climate Change in Basic Schools through The Application of Radec Learning Models - Basit, Rifqi Abdul; Maryani, Enok (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Currently, the planet earth is experiencing climate change, which is caused by the way of life of humans which is against the preservation of nature. Education must form humans who are aware of the problems that are happening so that students can be involved in solving these problems. This study aims to determine the extent to which the RADEC learning model is effective for critical skills on the problem of climate change in elementary schools. The number of participants in this study was 22 students. Data using tests and assessments based on critical assessment and problem management. The research method used in this research is quasi-experimental. The results showed that the students 'critical thinking skills training scores were 40.1 and the students' scores were 79.8. Then from the results of the critical and critical skills test it is known that p = 0.00Ë‚0.05. So, it can be denied that students' critical thinking skills regarding climate change issues have increased significantly after learning through the RADEC learning model.